2017
DOI: 10.1016/j.cell.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The In Vivo Architecture of the Exocyst Provides Structural Basis for Exocytosis

Abstract: Graphical AbstractHighlights d An integrative approach reconstructs protein complexes in 3D through live-cell imaging d We use this approach to reconstruct the exocyst complex bound to a vesicle in vivo d Exocyst is a stable complex and regulatory proteins target its multimerization site d We model how exocyst binds the vesicle allowing its contact with the plasma membrane In Brief Microscopy-derived spatial constraints allow modeling of the exocyst structure in vivo. Exocyst Plasma membrane Computer model by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 71 publications
(120 reference statements)
6
98
0
1
Order By: Relevance
“…To investigate the formation and disruption of Pol I transcription complexes in vivo, we used PICT (Protein interactions from Imaging Complexes after Translocation), a fluorescence microscopy technique to analyse protein interactions in living cells (Gallego et al, 2013; Picco et al, 2017). This technique uses cellular anchoring platforms tagged with both RFP and FK506-binding protein (anchor-RFP-FKBP) to recruit proteins tagged with FKBP-binding domain (bait-FRB).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the formation and disruption of Pol I transcription complexes in vivo, we used PICT (Protein interactions from Imaging Complexes after Translocation), a fluorescence microscopy technique to analyse protein interactions in living cells (Gallego et al, 2013; Picco et al, 2017). This technique uses cellular anchoring platforms tagged with both RFP and FK506-binding protein (anchor-RFP-FKBP) to recruit proteins tagged with FKBP-binding domain (bait-FRB).…”
Section: Resultsmentioning
confidence: 99%
“…[54] and Picco et al . [55] have attempted to resolve the yeast exocyst subunit connectivity map using co-purification and nanometer precision fluorescence microscopy, respectively. Interestingly, Heider and colleagues identified two sub-complexes, sub-complex I consisting of Sec3/EXOC1 (denoting yeast/human orthologs), Sec5/EXOC2, Sec6/EXOC3, Sec8/EXOC4 and sub-complex II consisting of Sec15/EXOC6, Sec10/EXOC5, Exo84/EXOC8 and Exo70/EXOC7.…”
Section: Resultsmentioning
confidence: 99%
“…Most recently, a model was proposed for the architecture of the exocyst and it was suggested that vesicles may be tethered by multiple exocyst complexes forming a ring surrounding the vesicle-plasma membrane contact zone where fusion occurs [33]. The multiplicity of tether extension events in the pulling experiments described here, may thus involve unfolding events from multiple exocyst complexes tethering a secretory vesicle.…”
Section: Discussionmentioning
confidence: 90%